Kebijakan Hukum Persaingan Usaha Terhadap Usaha Mikro, Kecil dan Menengah Di Era Digital - Utomo, Setiyo; Slamet Pribadi, Deny (Zaaken: Journal of Civil and Business Law, 2024)
The advancement of information and communication technology in the digital era has significantly transformed the business landscape. This transformation has the potential to create new opportunities and challenges across various sectors, including Micro, Small, and Medium Enterprises (MSMEs). In the digital era, MSMEs have greater access to the global market through e-commerce platforms and social networks, enabling them to reach customers worldwide. However, along with these opportunities, significant legal challenges arise that can impact the legal protection of MSMEs within the context of business competition. Factors such as the dominance of large corporations, complex regulations, privacy issues, and intense competition can hinder the progress of MSMEs. From the perspective of competition law, legal protection for MSMEs is a critical aspect. Competition law aims to promote fair competition, protect consumer interests, and prevent harmful practices like monopolies and oligopolies that affect smaller entities like MSMEs. The research method employed in this paper is a type of doctrinal research that systematically explains a regulation, focusing on legal principles and legal systems. This research intends to provide in-depth insights and relevant solutions to ensure that MSMEs can compete fairly and succeed in an increasingly competitive digital environment. The study aims to address questions related to legal protection and legal challenges faced by MSMEs in the digital era.